Diversity of Insect Species in PT Sumber Graha Sejahtera of Production Forest in West Wara District, Luwu Regency - Batari Putri, Andi Utami; Witno; Liana; Rian Badjang; Novi Herman Sada; Maria (Media Konservasi, 2025)
Insects are the most numerous groups of organisms in the phylum of Arthropods and have a very important role in the continuity of ecological functions. This study aims to determine the diversity of nocturnal and diurnal insect species in PT. Sumber Graha Sejahtera of production forest area in West Wara District. This study used 2 methods are plot and line transect. The traps used are Light traps for nocturnal insects used on 5 plot and Sweep Net for diurnal insects used on 3 line transect. The results showed that there were 36 species of insects consisting of 14 nocturnal species and 22 diurnal species. The diversity index of nocturnal insects were included in the medium category (2.57) with the highest population density found in the species Aedes albopictus which is 0.0160, while the diversity index of diurnal insects were included in the high category (3.02) with the highest population density found in the species Valanga nigricornis which is 0.0056.